Impact of patriarchal culture on violence against women and human development in the glass of milk committees of the Concepción district - Gomez Ferrer, Dora Elizabeth (2020)
Violence against women is the main problem for women on the national agenda, the Junín region ranks third nationally in marital violence. In the Concepción district, violence against women is a critical problem inasmuch as it has vulnerable sectors of its population, abandoned women, single mothers, illiterate women, migrants, women with low levels of education, among others. The majority of this population has been socialized in an authoritarian and violent culture, however, since the women of the glass of milk committees are permanently trained on their rights and against gender violence by the Ministry of Women and Vulnerable popul The objective of this investigation was to know the influence of the patriarchal culture in the generation of violence and the detriment of the integral human development of these women, for which the quantitative method was used, being a descriptive-explanatory investigation the Likert scale. The obtained result shows us that 15% of women manifest influence of the patriarchal culture that is expressed in the psychological and economic violence they suffer, obtaining a diminished human development in comparison with the percentage of women who are not victims of violence. The Likert scale applied reflects the opinions of women regarding patriarchal culture, gender violence, self-esteem and their empowerment.